Conventional Retail–Lower than Cost or Market. - Lindbeck, Rudolph S. (The Accounting Review, 1966)
Contemporary textbooks used for intermediate level accounting courses generally describe the results yielded through the application of the conventional retail inventory method as, essentially or approximately the same as the results yielded by application of the lower of cost or market rule. This assertion is supported by the argument that conventional retail results are always less than cost and always less than market. This argument could just as well support the claim that the use of the conventional retail method results in the most conservative inventory valuation. Undoubtedly the retail method has practical application in the retail trade, but pragmatic considerations should not serve as a basis for students' drawing unwarranted conclusions about application of the rule of cost or market or the retail inventory method. The author contends that conventional retail is not the same as lower of cost or market. If the basic assumptions underlying the conventional retail method are valid, then an analysis of the composition of the ending inventory will support this contention. The purpose of this discussion is to present such an analysis.